Molecular Genetic Characteristics of Plasmid-Borne mcr-9 in Salmonella enterica Serotype Typhimurium and Thompson in Zhejiang, China - Fan, Jianzhong; Cai, Heng; Fang, Youhong; He, Jintao; Zhang, Linghong; Xu, Qingye; Yang, Yunxing; Leptihn, Sebastian; Yu, Yunsong; Zhao, Dongdong; Hua, Xiaoting (Frontiers in Microbiology, 2022)
Salmonella enterica is a zoonotic food-borne pathogen threatening public health around the world. As is the case with many other pathogens, the spread of mobilized colistin resistance (mcr) alleles is of grave concern. In this study, totally 689 clinical Salmonella isolates were collected from a local hospital in Hangzhou, Zhejiang Province, China between 2009 and 2018. Resistance genes were screen by PCR. Two mcr-9-positive Salmonella strains S15 and S639 were identified which belong to serotype Typhimurium and Thompson, respectively. We observed that both mcr-9 genes were located on conjugative IncHI2 plasmids which encoded numerous resistance genes, likely facilitating the dissemination of mcr-9 by co-resistance mechanisms. The mcr-9 cassettes encoded on the two plasmids were not identical: downstream of the mcr-9 genes, we found IS1 on one plasmid (pS15), while the other had a WbuC-IS26 (pS639). Despite the presence of mcr-9 cassettes, the strains were not rendered colistin resistant. Yet, it is of epidemiological importance to implement surveillance to be able to observe and possibly control the spread of mcr-9 due to its potential to mediate resistance to the last-resort antibiotic colistin.